2010
DOI: 10.1007/s10211-010-0076-3
|View full text |Cite
|
Sign up to set email alerts
|

The gradual vocal responses to human-provoked discomfort in farmed silver foxes

Abstract: Vocal indicators of welfare have proven their use for many farmed and zoo animals and may be applied to farmed silver foxes as these animals display high vocal activity toward humans. Farmed silver foxes were selected mainly for fur, size, and litter sizes, but not for attitudes to people, so they are fearful of humans and have short-term welfare problems in their proximity. With a human approach test, we designed here the steady increase and decrease of fox–human distance and registered vocal responses of 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 62 publications
2
46
2
Order By: Relevance
“…Consistently to results of previous studies (Gogoleva et al, 2008, 2009, 2010b,c), in the presence of humans, Unselected and Aggressive foxes produced coughs and snorts and never emitted cackles and pants, while Tame foxes produced cackles and pants and never emitted coughs or snorts. Also, in accordance to previous data for comparison of vocal activities of these three strains under other test designs (Gogoleva et al, 2008, 2010b), Aggressive foxes showed higher proportions of time spent vocalizing throughout the test than Unselected or Tame foxes.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistently to results of previous studies (Gogoleva et al, 2008, 2009, 2010b,c), in the presence of humans, Unselected and Aggressive foxes produced coughs and snorts and never emitted cackles and pants, while Tame foxes produced cackles and pants and never emitted coughs or snorts. Also, in accordance to previous data for comparison of vocal activities of these three strains under other test designs (Gogoleva et al, 2008, 2010b), Aggressive foxes showed higher proportions of time spent vocalizing throughout the test than Unselected or Tame foxes.…”
Section: Discussionsupporting
confidence: 91%
“…The calling rate represents a reliable indicator of the degree of emotional arousal in silver foxes (Gogoleva et al, 2010b,c) and other mammals (Weary & Fraser, 1995; Weary et al, 1997; Rendall, 2003; Volodin et al, 2009). Therefore, we can suggest reasonable that the human appearance before the cage provokes the high level of emotional arousal of Tame foxes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current empirical research revealed cross-taxa similarities in the acoustical conveyance of emotions across different mammalian groups (e.g., [17], [18], [19], [20], [21], [22], [23]) which show similarities to prosodic cues in human speech and non-verbal vocalizations (e.g., [3], [6], [24], [25]). Various models were developed to characterize the universal relationship between the structure of vocalizations and their emotional content (e.g., [26], [27], [28], [29]).…”
Section: Introductionmentioning
confidence: 99%
“…Wild-type Unselected foxes produced cough and snort toward humans similarly to Aggressive foxes (Gogoleva et al, 2008a,b, 2010). This suggests that the directional selection for aggressiveness toward humans did not affect vocalization toward humans in the silver fox, whilst the directional selection for tameness, mimicking the process of historical domestication targeted at the tolerance of animals toward humans (Belyaev, 1979), drastically affected vocalization toward humans in the silver fox.…”
Section: Introductionmentioning
confidence: 98%